Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Suganuma, Yusuke; Kaneda, Heitaro; Mas e Braga, Martim; Ishiwa, Takeshige; Koyama, Takushi; Newall, Jennifer; Okuno, Jun'ichi; Obase, Takashi; Saito, Fuyuki; Rogozhina, Irina; Andersen, Jane; Kawamata, Moto; et al. (Communications Earth & Environment, 2023)
Funding: The field campaign was supported by the Japanese Antarctic Research program, the Norwegian Polar Institute/NARE, and SANAE IV Station. The permission for rock sampling in Antarctica has been approved by the ministry of the Environment, Japan. The study was supported by the JSPS Kakenhi (16H05739; 17H06321; 19H00728; 21H01173), the TOREY Science Foundation, NIPR through Advanced Project (KP-1), GRAntarctic, and MAGIC-DML (through grants from Stockholm University, the Norwegian Polar Institute – NARE, the US National Science Foundation (OPP-1542930), the Swedish Research Council, and the German Research Foundation). The high-resolution model experiments were enabled by resources provided by the Swedish National Infrastructure for Computing (SNIC) at the National Supercomputer Centre (NSC) partially funded by the Swedish Research Council through grant agreement no. 2018-05973. The East Antarctic Ice Sheet stores a vast amount of freshwater, which makes it the single largest potential contributor to future sea-level rise. However, the lack of well-constrained geological records of past ice sheet changes impedes model validation, hampers mass balance estimates, and inhibits examination of ice loss mechanisms. Here we identify rapid ice-sheet thinning in coastal Dronning Maud Land from Early to Middle Holocene (9000–5000 years ago) using a deglacial chronology based on in situ cosmogenic nuclide surface exposure dates from central Dronning Maud Land, in concert with numerical simulations of regional and continental ice-sheet evolution. Regional sea-level changes reproduced from our refined ice-load history show a highstand at 9000–8000 years ago. We propose that sea-level rise and a concomitant influx of warmer Circumpolar Deep Water triggered ice shelf breakup via the marine ice sheet instability mechanism, which led to rapid thinning of upstream coastal ice sheet sectors. Peer reviewed